TeleMeios as a Virtual Environment and their possibilities in Hybrid Education - Meneses Saldanha Nepomuceno, Lara; Santos Silva, André; de Oliveira Xavier, Daniele; de Castro Barbosa, Jessica; Uchôa Araújo, Ana Cláudia; Borges Neto, Hermínio; Martins Torres, Antonia Lis de Maria (International Journal for Innovation Education and Research, 2019)
The discussion contemplates the construction and development of collaborative digital tools to support distance teaching, with its origins still in the 2000s, within the scope of the Multimeios Research Laboratory, linked to the Faculty of Education (FACED) of UFC, located at city of Fortaleza / Ceará / Brazil. Thus, it aims to analyze the experiences of construction and (re) structuring of the TeleMeios Virtual Teaching Environment (VTE) and its adaptive possibilities in a hybrid context, with a view to subsidizing formative actions in which learners and teachers can have access to virtual experiences in the learning environment which play the role of protagonists. As theoretical reference, there are the studies of Borges (2009), Jucá (2011), Moran (2015), Bacich; Tanzi Neto; Trevisani (2015) among others, which discuss about teaching and hybrid education, digital information and communication technologies, as well as other themes involving teaching and virtual and classroom learning. The research is bibliographical, of a qualitative nature, anchored in Lakatos and Marconi (2002), which makes use of publications such as textbooks, scientific articles, reviews, which deal with the subject. Among the findings, it can be highlighted that the TeleMeios environment has a formative potential to be explored and investigated, focusing on the structural and pedagogical design of virtual environments that surpass the concept of content repository and the idea of students as receptacles of knowledge. and teachers, as sole holders of knowledge.